Patient Experience: Innovating the Application of LAFKI Concept in Person-Centred Care at Healthcare Facilities - Rumintjap, Friedrich M; Wahyudi, Ahyar; Meher, Cashtri; Yuliana, Dewi; Yuwanto, Listyo (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study evaluates the implementation of the Indonesian Healthcare Facility Accreditation Agency (LAFKI)'s Person-Centred Care (PCC) principles in healthcare settings. Focusing on patient experiences, the research addresses the effectiveness of PCC practices in enhancing health outcomes and patient satisfaction. The methodology employed involves a quantitative descriptive design, gathering data through questionnaires distributed via Google Forms to participants selected through purposive sampling from hospitals, clinics, and puskesmas. Findings indicate that while a majority of patients felt treated as unique individuals, a significant gap exists in respecting cultural values and beliefs during the decision-making process. The study highlights the need for healthcare providers to improve cultural sensitivity and patient engagement to bridge the ideological and practical implementation of PCC. The research contributes to the empirical literature by identifying barriers to effective PCC implementation and offering evidence-based recommendations for healthcare facilities to enhance their services. This aligns with LAFKI's goal of not just meeting but exceeding standards in providing holistic, person-centred care.